2007
DOI: 10.1523/jneurosci.4693-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Contact Points during Multidigit Grasping: Effect of Predictability of Object Center of Mass Location

Abstract: It has been shown that when subjects can predict object properties [e.g., weight or center of mass (CM)], fingertip forces are appropriately scaled before the object is lifted, i.e., before somatosensory feedback can be processed. However, it is not known whether subjects, in addition to these anticipatory force mechanisms, exploit the ability to choose where digits can be placed to facilitate object manipulation. We addressed this question by asking subjects to reach and grasp an object whose CM was changed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 26 publications
8
135
1
2
Order By: Relevance
“…Previous work has shown that this is best accomplished by generating an opposing torque before the object is lifted (Salimi et al 2000). We found that subjects learn to generate such compensatory torque by modulating both digit forces and placement to object CM prior to object liftoff (Fu et al , 2011Lukos et al 2007Lukos et al , 2008. Furthermore, Lukos et al (2008) reported evidence for independent control mechanisms of digit placement and force planning in response to random changes in object CM.…”
mentioning
confidence: 63%
“…Previous work has shown that this is best accomplished by generating an opposing torque before the object is lifted (Salimi et al 2000). We found that subjects learn to generate such compensatory torque by modulating both digit forces and placement to object CM prior to object liftoff (Fu et al , 2011Lukos et al 2007Lukos et al , 2008. Furthermore, Lukos et al (2008) reported evidence for independent control mechanisms of digit placement and force planning in response to random changes in object CM.…”
mentioning
confidence: 63%
“…One possible working hypothesis is that intermediate area 12r contributes to the exploitation of nonspatial memory-based or working memory information related to object properties (e.g., weight, center of mass, fragility, texture) or identity, for controlling object-oriented actions. This information, based on implicit (sensorimotor memories) or explicit knowledge, could be used for grasping selection and anticipatory force control or for updating motor programs (Johansson and Cole, 1992;Lukos et al, 2007Lukos et al, , 2008Loh et al, 2010). Intermediate area 12r could also contribute to tactile object recognition, which requires retrieving memorized information about object properties and identity.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…One paradigm that has been found useful for such studies involves lifting an object whose weight distribution is asymmetric, thus requiring the digits to exert not only a net vertical force but also a torque to prevent rolling of the object (Goodwin et al, 1998;Salimi et al, 2000Salimi et al, , 2003Lukos et al, 2007Lukos et al, , 2008. Presented with this task, subjects learn to modulate digit forces as a function of digit placement to exert a compensatory torque in an anticipatory fashion (i.e., before lifting the object) .…”
Section: Introductionmentioning
confidence: 99%